Implementasi Metode RAD pada Sistem Pemesanan Makanan dan Minuman Berbasis Web dengan QR Code - Imam Syazali Lubis; Siti Aliyah (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2026)
This study was conducted to address operational issues at Kafe Kaffeine, which still relied on a semi-computerized ordering process that caused service delays, data inaccuracies, and inefficiencies in generating daily sales reports. The objective of this research is to develop a web-based food and beverage ordering system integrated with QR Code technology to improve service speed and data accuracy. The Rapid Application Development (RAD) method was employed due to its iterative nature and its ability to involve users throughout each development stage. The system was developed using PHP, MySQL, HTML, CSS, and JavaScript, and evaluated through black-box testing. The results indicate that QR Code integration enables customers to place orders independently, reduces input errors, and accelerates transaction flow. Furthermore, the system automates sales recording and provides real-time reporting, thereby enhancing operational efficiency and service quality in culinary SMEs.